Pharmacological Chronic Heart Failure Therapy in Children. Focus on Differentiated Medical Drug Support - Esmaeili, Anoosh; Schranz, Dietmar (Cardiology and Cardiovascular Medicine, 2020)
The etiology of pediatric heart failure is heterogenous. Missing evidence-based studies lead to symptom-based therapies. Regarding children’s life expectancy, heart regenerative strategies are required. Pathophysiological differences such as the dependence of the ventricles on the preload, the tendency towards peripheral centralization with predominantly catecholamine-controlled circulatory regulation as well as age and disease-related differences in the myocardial ß-receptor physiology require individualized precision medicine with the concept of a “responder phenotype”. First-line therapy with diuretics for chronic heart failure is not indicated. Inadequate diuretic therapy is a common reason that anti-adrenergic and renin-angiotensin-aldosterone antagonists are not or only insufficiently administered. Regarding pediatric dilated cardiomyopathy, selective ß1-blockers and tissue ACE-inhibitors are indicated primarily for their activity and side-effect profile, as well as for reasons of heart regeneration. A high-selective ß1-blocker, (bisoprolol) protects against noradrenaline-associated myocytic apoptosis and necrosis, but allows β2-receptor mediated myocardial regeneration. A reduced heart rate lowers myocardial oxygen consumption and extends the diastolic filling and coronary perfusion time. Despite the fact that the risk of cardiac fibrosis in infants is lower, the combination of bisoprolol-lisinopril-spironolactone (B-L-S) is still beneficial. Effective B-L-S doses can reduce systemic vascular resistance by ensuring myocardial perfusion pressure due to an adequate intravascular volume (preload). Almost identical daily doses of bisoprolol and lisinopril (0.1-0.2 (0.4) mg/kg/day) and 0.5-1 (- 2) mg / kg spironolactone enable a high level of compliance in the treatment by the parents or young patients. In summary, individualized heart failure therapy is the prerequisite for further regenerativ